TINJAUAN TERHADAP POLITIK HUKUM PEMERINTAH DALAM PENYELESAIAN KEKERASAN TERHADAP ANAK DIDIK DI LINGKUNGAN SEKOLAH DARI ASPEK UNDANG – UNDANG PERLINDUNGAN ANAK (UNDANG-UNDANG NOMOR 23 TAHUN 2002 JUNCTO UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 35 TAHUN 2014) - Ariza Irnanda (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
AbstrackAriza Irnanda, The issues of education in Indonesia at this present is very complex exactly, which is from fund of education that is not proportional, to every deliquency as a criminal act juridically. In a simple sense, educational offense refers to every offense that is happened in educational field. Absolutely, it shows that educational field is not free of guilty, as people think it up till now.An educational offense which is being main focus of this research is a offense that is done by teachers in carrying out their task/proffesion. As we know, sometimes, teachers in carrying out their proffesion making acts that is juridically break the law and inflict their student, for example: Give them punishment like hitting, isolating, or suspending, etc as one of disciplinary action to reach out any certainly educational aims. This research used juridical – normative approach. The data which are relevance to this research have been focused to a secondary data mostly through literate study. Then, those are analyzed as descriptive – analysis.There are three results have been concluded from this research. The first, generally, a kind of educational offense and classification of a criminal act that is done by teacher in carrying out their task. The second, what is  the pupose of government in drafting UU Nomor 23 Tahun 2002 about A Children Protection. Both is used to control 2 (two) kind of criminal act that teachers do in carrying out their task, it called: a pure criminal act and criminal act as reflection of disciplinary action. The third, what the role of government in dealing with criminal offenses. In criminal act, those acts have been focused to “Tuchtrech” as a justified reason. In the case of criminal responsibility, for humanity and justice, is reccomended Judge’s effort to forgive teacher’s fault which is called “rechterlijkpardon”. A criminal sanction. Based on flexibility and modification idea, a type of sanction is pointed to double track system, that is : treatment and sentence. Beside that, it’s reccommeded a possibility to lighten or make heavier sanction for a specially and rationally reasons.